The Potential of Traditional Food in Developing Creative Culinary Tourism in the City of Palangka Raya - Widiya Widiya; Putu Sucita Yanthy; Ni Made Sofia Wijaya (Cita Konsultindo Research Center, 2024)
Traditional food as one of the culinary tourism attractions. For tourists, appreciating and enjoying the traditional food is a way to experience the uniqueness of a destination which they visit. Traditional food is often a reflection of cultural richness, its distinctive and unique taste is often the main attraction fortourists who want to experience the diversity of local culinary delights in an area. This research aims to identify the potential of traditional food as a creative culinary tourism product in Palangka Raya City and analyze the development of traditional food as creative culinary tourism in Palangka Raya City The research method used is qualitative with a qualitative descriptive approach. Data collection methods were carried out through observation, interviews and literature studies. The results of this research show that there is potential for traditional food that can be developed in Palangka Raya City, namely 6 types of traditional food, 1 type of traditional drink, 2 types of snacks and 5 types of typical souvenirs that have their own taste. The development of traditional food as a creative culinary tourism attraction in Palangka Raya City such as innovation, combining modern cooking techniques with traditional recipes, and through the Isen Mulang Festival and Nusantara Culinary Festival events which can create interesting and authentic creative culinary tourism experiences. The implication of this research is to encourage the development of culinary tourism by implementing alternative strategies to increase the preservation of local cultural identity, promotion and marketing and increase economic growth for local communities in improving the quality of life